Thermal Manipulation During Embryogenesis Impacts H3K4me3 and H3K27me3 Histone Marks in Chicken Hypothalamus - David, Sarah-Anne; Vitorino Carvalho, Anaïs; Gimonnet, Coralie; Brionne, Aurélien; Hennequet-Antier, Christelle; Piégu, Benoît; Crochet, Sabine; Couroussé, Nathalie; Bordeau, Thierry; Bigot, Yves; Collin, Anne; Coustham, Vincent (Frontiers in Genetics, 2019)
Changes in gene activity through epigenetic alterations induced by early environmental challenges during embryogenesis are known to impact the phenotype, health and disease risk of animals. Learning how environmental cues translate into persisting epigenetic memory may open new doors to improve robustness and resilience of developing animals. It was previously shown that the heat tolerance of male broiler chickens was improved by cyclically elevating the egg incubation temperature. The embryonic thermal manipulation enhanced gene expression response in muscle (P. major) when animals were heat challenged at slaughter age, 35 days post-hatch. However, the molecular mechanisms underlying this phenomenon remain unknown. Here we investigated the genome-wide distribution in hypothalamus and muscle of two histone post-translational modifications, H3K4me3 and H3K27me3, known to contribute to the environmental memory in eukaryotes. We found 785 H3K4me3 and 148 H3K27me3 differential peaks in the hypothalamus encompassing genes involved in neurodevelopmental, metabolic and gene regulation functions. Interestingly, few differences were identified in the muscle for which differential gene expression was previously described. These results demonstrate that the response to embryonic thermal manipulation in chicken is mediated at least in part by epigenetic changes in the hypothalamus that may contribute to the later-life thermal acclimation.